A comparison of union rates and complications between single screw and double screw fixation of sliding calcaneal osteotomy. Issue 1 (February 2019) - SahraNavard, Bahman; Hudson, Parke W.; de Cesar Netto, Cesar; Wills, Bradley W.; Araoye, Ibukunoluwa B.; Bergstresser, Shelby; Cone, Brent M.; Shah, Ashish
Highlights: Compared union and complications of 1 and 2 screw fixation of calcaneal osteotomy. No significant difference between single and double screw fixation. No significant difference between short and extended incisions. Increased complications, specifically hardware removal, with headed screws. Abstract: Background: The number of screws used for sliding calcaneal osteotomy fixation has not been examined in the literature. The purpose of this paper is to examine this topic. Methods: Retrospective chart review was performed on 190 patients who met selection criteria. We compared complication risk for single versus double screw, headed versus headless screw, and short versus longitudinal incision cases. Results: The mean age was 48.4 (18–83) years and average follow up was 28 (12–150) weeks. All cases achieved radiographic union. Overall complication rate was 19.5% (37/190). Risk of complication did not differ significantly between single and double screw (RR: 1.170; 95% CI: 0.66–2.09; p = 0.594) or short and extended incision groups (RR: 0.868; 95% CI: 0.42–1.80; p = 0.704). Risk of complication differed significantly between headed and headless screw fixation (RR: 5.558; 95% CI: 2.69–11.50; p < 0.0001). Conclusions: Single screw fixation of sliding calcaneal osteotomy achieves similar outcomes as double screw fixation. Headless screws are advantageous for minimizing hardware pain and subsequent hardware removal.